Pengaruh Penerapan Google Earth Sebagai Media Pembelajaran Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Geografi - Nindiawati Daud; Fitryane Lihawa; Sri Maryati (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to determine the effect of using Google Earth as a learning medium on students’ learning outcomes in Geography at SMA Negeri 4 Gorontalo. The research employed a quasi-experimental design with a one-group pretest-posttest model. The independent variable in this study was the use of Google Earth, while the dependent variable was the students’ learning outcomes. Data collection techniques included observation, documentation, and pretest-posttest assessments. The data were analyzed using normality tests, paired sample t-tests, gain index analysis, and descriptive statistics. The reliability test showed an alpha coefficient of 0.892, indicating high reliability. The gain index reached 0.73 or 73.10%, categorized as moderate, which demonstrates that Google Earth is effective in improving students’ understanding of remote sensing materials related to land use. The results of the study indicate that Google Earth is effective as a visual-spatial learning medium that enhances students’ conceptual understanding of remote sensing materials, particularly in the context of land use. This study concludes that the use of Google Earth has a positive effect on students’ learning outcomes.